Effect of Shape, Density, and an Array of Dimples on the Friction and Wear Performance of Laser Textured Bearing Steel under Dry Sliding - Kumar M.; Ranjan V.; Tyagi R. (My University, 2025)
The present study is directed to reveal the effect of density and shape of the dimples on the friction and wear characteristics of textured bearing steel (100Cr6) under dry sliding conditions. One untextured and four laser-textured disks of 100Cr6 steel with circular and bi-triangular dimples having 7 and 20% density, respectively, in the spiral layout were tested using a pin-on-disk unidirectional tribometer against a 100Cr6 pin having a flat surface with rounded corners under flat-on-flat configuration. The tests were carried at different speeds of 0.2, 0.6, and 1 m/s at a constant load of 15 N. The results indicate that a higher density of bi-triangular dimples had less wear and a lower coefficient of friction compared to untextured disk or disk with circular dimples, particularly at a relatively higher speed. This has been attributed to a relatively higher number of dimples in the contact zone in case of a spiral array, which increases the entrapment of more wear particles leading to a reduction in wear. The friction coefficient had a relatively higher value at a relatively lower speed but decreased at the highest speed of 1.0 m/s used in the present study. The results suggest that dimples may not be too effective under dry contact because they lose their effectiveness to trap wear debris after getting filled. © 2020, ASM International.